Can the use of infrared vein finder help refine venipuncture? - Mansoor, Noman; Warsi, Aimen (Journal of the Pakistan Medical Association, 2023)
Madam, Venipuncture is one of the most frequent invasive procedures carried out in hospitals. It involves inserting a needle into a vein in order to extract a blood sample for hematological, biochemical, or bacteriological investigation. [1]. Although the most common procedure, it does come with its drawbacks. A study investigating more than a million venipuncture procedures between 2005 and 2014 revealed that one in every 3700 persons (0.027%) faced post-venipuncture complications [2]. Although the number is small, it cannot be disregarded. Another study found that mild bruising and hematoma were prevalent, accounting for 12.3% of all venipunctures, with minor bruising being the most frequent. Serious complications were also observed in 3.4% of patients. In 2.6% of cases, there was hypotension and diaphoresis. Syncope occurred in around 1% of patients [3]. A study also showed that six patients out of 80,000 seen in a blood-transfusion center over two years had painful peripheral-nerve injuries after venipuncture in the antecubital fossa [4]. Other possible complications include petechiae, extravasations, edema, thrombosis, and arterial puncture [5]. Although the number of post-venipuncture complications is small, it does persist and needs to be addressed. These complications can be reduced to a significant extent by the use of an infrared vein finder. An infrared vein finder is a medical device that uses infrared light to locate veins beneath the skin. The light passes through the skin and reflects off the blood vessels beneath. An optical sensor then records the reflected light, which produces an image of the veins that can be viewed on a display screen. [6]. When placing IVs or taking blood samples, they aid in greater accuracy and save time because veins can be found quickly and easily. Since needles can be placed into veins more precisely, they can lessen pain and discomfort for patients. They might also lessen the number of issues that can arise when drawing blood or inserting IVs. The near-infrared technology is also useful for finding the vein for cannulation, therapy, and other medical purposes at a very low cost, for pediatric and elderly patients, as well as others with challenging venous access. [7]. Their use in emergency settings can be vital, as they allow faster vein access hence saving critical time. They can be operated by anyone who has received proper training because they are uncomplicated to operate. They are also reasonably priced. ---Continue